A Mathematical Model of Brain Tumor with Glia-Neurons Interaction and Chemo- Virotherapy Treatment - Sujitha, S.; Jayakumar, T.; Maheskumar, D.; Bharathi, D. Prasantha; Kaviyan, E. Vargees (Discontinuity, Nonlinearity, and Complexity, 2026)
This paper investigates the brain tumor model describing the interactions between Glial cells, Sensitive Glioma cells, Resistant Glioma cells, and Neurons with Chemo-Virotherapy treatment. Chemo-Virotherapy has emerged as a promising novel cancer treatment to destroy glioma cells. The main aim is to kill tumor cells using virus-like Adenovirus and Herpes simplex virus-1 by virotherapy with Chemotherapy sessions. Stability Analysis is discussed under four categories: without any treatment, with chemotherapy treatment, with virotherapy treatment, and chemo-virotherapy treatment. Without any treatment, stability Analysis of the model shows that a tumor would grow to its maximum size. In the case of chemotherapy treatment, analysis of the model shows that the growth of resistant glioma cells increases at a quicker rate than healthy cells. Furthermore, virotherapy may not be able to remove glioma cells on its own, but if high viral potency viruses are used, they will reduce chemotherapy sessions. This analysis suggests that the combination therapy could lead to tremendous success in treating gliomas.